-33+21=-2x+5x

Simple and best practice solution for -33+21=-2x+5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33+21=-2x+5x equation:


Simplifying
-33 + 21 = -2x + 5x

Combine like terms: -33 + 21 = -12
-12 = -2x + 5x

Combine like terms: -2x + 5x = 3x
-12 = 3x

Solving
-12 = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-12 + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
-12 + -3x = 0

Add '12' to each side of the equation.
-12 + 12 + -3x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + -3x = 0 + 12
-3x = 0 + 12

Combine like terms: 0 + 12 = 12
-3x = 12

Divide each side by '-3'.
x = -4

Simplifying
x = -4

See similar equations:

| 2x+4+50=90 | | 100-5x=50 | | 3-2x=-2x+1 | | 4j-2j+10=j | | 8xn+4=80 | | 6x-2+3x=61 | | 13x+4y=5.88 | | -7=3x+4 | | 48=15x-3x | | 3(n+5)=6-3(n-7) | | -3x+5y-7=0 | | 8(1.5+.5y)-4y=12 | | 5-2(x+5)=40 | | 4x(126)= | | 20-5s=8 | | x^2(x-3)(x^2-9)(x^2+4)=0 | | W=Fa+FB | | 6x^2(36)= | | x^2+18x+y^2=-17 | | (4x+3)-5=5(x+4) | | x*12+-42+85=246 | | 74=10+4x | | 5y-7+y+27=5y+20-3y | | 7(0)-2(6)=12 | | x^2+y^2+18x+17=0 | | x(x)=16316 | | 190=-8+9x | | 8x-14=-16 | | 7(5x+8)=-x+4 | | 0.10(y-9)+0.12y=0.18y-0.07(10) | | 7(5x+8)=-x+4 | | 8(2x+1)=7x+7 |

Equations solver categories